Theoretical Calculation Guided Design of Single-Atom Catalysts toward Fast Kinetic and Long-Life Li-S Batteries - Zhou, G.; Zhao, Shiyong; Wang, T.; Yang, S.Z.; Johannessen, B.; Chen, H.; Liu, C.; Ye, Y.; Wu, Y.; Peng, Y.; Liu, C.; Jiang, San Ping; et al. (AMER CHEMICAL SOC, 2020)
Lithium-sulfur (Li-S) batteries are promising next-generation energy storage technologies due to their high theoretical energy density, environmental friendliness, and low cost. However, low conductivity of sulfur species, dissolution of polysulfides, poor conversion from sulfur reduction, and lithium sulfide (Li2S) oxidation reactions during discharge-charge processes hinder their practical applications. Herein, under the guidance of density functional theory calculations, we have successfully synthesized large-scale single atom vanadium catalysts seeded on graphene to achieve high sulfur content (80 wt % sulfur), fast kinetic (a capacity of 645 mAh g-1 at 3 C rate), and long-life Li-S batteries. Both forward (sulfur reduction) and reverse reactions (Li2S oxidation) are significantly improved by the single atom catalysts. This finding is confirmed by experimental results and consistent with theoretical calculations. The ability of single metal atoms to effectively trap the dissolved lithium polysulfides (LiPSs) and catalytically convert the LiPSs/Li2S during cycling significantly improved sulfur utilization, rate capability, and cycling life. Our work demonstrates an efficient design pathway for single atom catalysts and provides solutions for the development of high energy/power density Li-S batteries.